Effect of fillet temperature on lipoxygenase activity in sardine mince with and without milk protein concentrate. (April 2018) - Tolasa Yılmaz, Şebnem; Çaklı, Şükran; Şen Yılmaz, Evren Burcu; Kırlangıç, Fatih; Lee, Chong
Abstract: The antioxidant effect of milk protein concentrate (MPC) was investigated as a function of fillet temperature on lipoxygenase (LOX) activity, formation of thiobarbituric acid reactive substances (TBARS) and omega (ω)-3 fatty acid retention in fresh and 3 month frozen stored sardine mince with or without MPC. The addition of 4% MPC to sardine mince at 0 min, at all temperatures, resulted in significantly lower LOX activity and TBARS values (μmoles malonaldehyde/100 g tissue) compared to the addition of MPC after 20 min holding or without MPC after 3-month frozen storage. These results show the importance of addition of antioxidants immediately after mincing and keeping the mince chilled before freezing. The addition of MPC did not protect omega (ω)-3 fatty acids from enzymatic oxidation but in general higher amounts of EPA and DHA were observed at 0 °C compared to 5 °C. An increase in the temperature of sardine fillet increased the LOX activity resulting in enzymatic lipid oxidation. The mechanically prepared mince from oily fish should be prepared at a temperature lowest possible with antioxidants added immediately upon mincing. Highlights: An increase in fish fillet temperature increases the rate of lipid degradation. Use of antioxidant immediately upon mincing help to retard LOX initiated oxidation. Antioxidants may control the LOX-mediated oxidation in frozen stored fish mince.